2012
DOI: 10.1155/2012/121360
|View full text |Cite
|
Sign up to set email alerts
|

Experts' Encounters in Antenatal Diabetes Care: A Descriptive Study of Verbal Communication in Midwife-Led Consultations

Abstract: Aim. We regard consultations as cocreated communicatively by the parties involved. In this paper on verbal communication in midwife-led consultations, we consequently focus on the actual conversation taking place between the midwife and the pregnant woman with diabetes, especially on those sequences where the pregnant woman initiated a topic of concern in the conversation. Methods. This paper was undertaken in four hospital outpatient clinics in Norway. Ten antenatal consultations between midwives and pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Evidence among health professionals has demonstrated training packages increase women's self-efficacy [ 37 ] and the potential inclusion for mobile health technology, so that women can access repeated information at their own convenience [ 38 ]. Other studies have revealed that providing empathy [ 39 ], emotional support, and understanding different ways of communicating [ 40 ] may create opportunities to share perspectives and overcome barriers of fear and anxiety. Effective communication and education were facilitators to increase motivation and encourage women to participate with the current dietetic service.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence among health professionals has demonstrated training packages increase women's self-efficacy [ 37 ] and the potential inclusion for mobile health technology, so that women can access repeated information at their own convenience [ 38 ]. Other studies have revealed that providing empathy [ 39 ], emotional support, and understanding different ways of communicating [ 40 ] may create opportunities to share perspectives and overcome barriers of fear and anxiety. Effective communication and education were facilitators to increase motivation and encourage women to participate with the current dietetic service.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Five hospital clinics were initially approached; of these, four agreed to participate in the study. The head midwife at each setting provided contact with midwives at the S-ANC who then were given written and oral information about the study by the first author.…”
Section: Methodsmentioning
confidence: 99%
“…When the midwife ‘palpates the abdomen’ to check the foetus, a kind of existential meaning is conveyed in expecting a baby and becoming a mother. In Furskog Risa, 2017 view, this bodily, ‘hands‐on’ communicative activity opens up for the woman to share comments and questions, and for the midwife, palpating the abdomen (Leopold's manoeuvre) can be seen as a profession‐specific communicative tool. This is an example of communicative strategies that are situationally adapted.…”
Section: Types Of Person‐centred Conversations Relevant To Nursing An...mentioning
confidence: 99%
“…The instruction is co-created (Figure 1c) and not linear in the sense of 'sender-receiver' (Figure 1a). (Furskog Risa, 2017). The women visited the midwives every 14 days for guidance and to check their blood sugar levels and the progress of the pregnancy.…”
Section: Instructive Conversationsmentioning
confidence: 99%